Pengaruh kesadaran merek dan diskon harga terhadap niat pembelian dengan mediasi citra Restoran Seafood New Javana di Surabaya - Haryo Agung Prasetyo; Soni Harsono (Journal of Business & Banking, 2015)
The purpose of this research was to examine The Effect of Brand Awareness and Price Discount on Purchase Intention as mediated by the image of Seafood Restaurant New Javana in Surabaya. The data were collected by means of questionnaire for getting the response from the respondents on the 76 people. Sampling method is the Accidental Sampling conducted by questionnaire that is spread in a Restaurant Seafood New Java-na. Analysis technique used to test the relation of independent variables, mediating vari-able, and dependent variable is the Path Analysis with SPSS software for 16 Windows. This research shows that brand awareness and price discounts are significant and simul-taneous partial influence on the image of the restaurant. Brand awareness and purchase intent affect significantly, either directly or with the mediated image of the restaurant. Discount price does not affect significantly purchase intention. However, the discount price does not affect significantly purchase intent. But, the discount price can affect pur-chase intent significantly mediated the image of the restaurant.